STRATEGI KREATIF DALAM MERANCANG KURIKULUM PENDIDIKAN AGAMA ISLAM (PAI) DI SEKOLAH DAN MADRASAH - Azet Sampurna; Agus Pahrudin; Agus Jatmiko; Koderi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The Islamic Religious Education (PAI) curriculum designed in schools and madrasas faces difficulties in balancing traditional values with the needs of modern education. The aim of this research is to discover and suggest innovative methods for creating an Islamic Religious Education (PAI) curriculum that combines modern pedagogical methods while maintaining Islamic values. This study employs a qualitative methodology through document analysis, interviews with teachers, and case studies in several selected institutions. The research results show that new methods such as blended learning, thematic teaching, and community-based activities enhance the relevance and appeal of the PAI curriculum. Additionally, this study emphasizes the importance of collaborative efforts between educators, curriculum developers, and religious authorities to ensure the curriculum meets both academic and spiritual needs. This research concludes that creative strategies in curriculum design can create a dynamic and effective Islamic education that prepares students to face future challenges without sacrificing their faith and values.